Augmented Reality - Yngvesson, Johan; Magnusson, Johannes (My University, 2019)
A prototype of a mobile quiz application, called “Treasures of Lindängen”, has been developed by Semcon in cooperation with Malmö city since june 2017. Together they have a vision to form positive habits resulting in improved educational outcomes and physical health. The goal is first and foremost to help schools in vulnerable areas of the city. The application is supposed to motivate school children to achieve better results in their studies while they are engaged and entertained. The purpose of this project is to enhance the gaming experience of the application through the use of gamification, and to investigate how this can be achieved using augmented reality.. In most cases, there was no major contrast in the statistics that tested the older and the later version. Further usability tests need to be done in order to draw any conclusions.The aim of the project will be the visualisation of quiz questions in AR.
Keywords: Gamification; Augmented reality; Android development